Meninjau Posisi Mitra Ojek Online Dalam Hukum Ketenagakerjaan di Indonesia - Rinaldi Adie Putro; Agus Ariadi (Dialog Legal: Jurnal Syariah, Jurisprudensi dan Tata Negara, 2026)
Based on the online motorcycle taxi (ojek online) sector in Indonesia, such as Gojek and Grab, this has given rise to a new form of working relationship that cannot be fully defined as an ordinary employment relationship. Partnering with online motorcycle taxi platforms is based solely on a partnership agreement rather than an employment agreement, meaning these partners do not receive the legal protection granted to workers or laborers as regulated under Manpower Law No. 13 of 2003 and its amendment under the Job Creation Law. This research aims to examine the legal position of online motorcycle taxi partners within Indonesia's labor law system and to identify the gaps in their legal protection. This research employs a normative juridical research method, comprising legislative, conceptual, and comparative legal approaches. The research findings indicate that, structurally, digital platforms and driver-partners exist in a relationship of subordination similar to that found in an employment relationship, yet the relationship formally takes the shape of a partnership. This situation creates a legal protection vacuum for partners, who face risks of income insecurity, inadequate social security, and the absence of a clear process for resolving disputes. Therefore, this research recommends establishing a distinct legal status for digital platform workers in Indonesia, in line with the concept of a third category of worker, or independent worker, applied in several other countries.